Fathers and Daughters in the Hebrew Bible. By Johanna Stiebert - Ostriker, Alicia (The journal of theological studies, 2013)
A Conventional view of father–daughter relationships in the Hebrew Bible, at least among feminist critics, is that daughter-figures are mostly absent from the text, and when present are helpless, passive, nameless, ‘expendable’ objects typically subject to abuse and violence. Commonly cited are what Phyllis Trible has called ‘texts of terror’: episodes in which Lot offers his virgin daughters to a mob, Jacob’s daughter Dinah is a pawn to the men in her family, Jephthah offers his virgin daughter as a human sacrifice, David fails to respond to the rape of his daughter Tamar.